Saudi native chicken response to embryonic thermal manipulation: Comparative morphometric analysis of myofiber diameter of the pectoral and thigh muscles - Ibrahim Albokhadaim (Open Veterinary Journal)
Background: Native Saudi chickens have the genetic capacity to develop well and produce eggs in hot environments, allowing them to withstand heat stress. Thermal alteration is one of the most significant suggested tactics that aim to improve muscle growth and growth performance during embryogenesis genetically.